The influence of Southern Ocean winds on the North Atlantic carbon sink. Issue 6 (8th June 2016) - Bronselaer, Ben; Zanna, Laure; Munday, David R.; Lowe, Jason
Abstract: Observed and predicted increases in Southern Ocean winds are thought to upwell deep ocean carbon and increase atmospheric CO2 . However, Southern Ocean dynamics affect biogeochemistry and circulation pathways on a global scale. Using idealized Massachusetts Institute of Technology General Circulation Model (MITgcm) simulations, we demonstrate that an increase in Southern Ocean winds reduces the carbon sink in the North Atlantic subpolar gyre. The increase in atmospheric CO2 due to the reduction of the North Atlantic carbon sink is shown to be of the same magnitude as the increase in atmospheric CO2 due to Southern Ocean outgassing. The mechanism can be described as follows: The increase in Southern Ocean winds leads to an increase in upper ocean northward nutrient transport. Biological productivity is therefore enhanced in the tropics, which alters the chemistry of the subthermocline waters that are ultimately upwelled in the subpolar gyre. The results demonstrate the influence of Southern Ocean winds on the North Atlantic carbon sink and show that the effect of Southern Ocean winds on atmospheric CO2 is likely twice as large as previously thought in past, present, and future climates. Key Points: Increased Southern Ocean winds reduce the North Atlantic carbon sink The effect of Southern Ocean winds on atmospheric p CO2 is doubled by the nonlocal feedback Atlantic tropical biology affects the North Atlantic subpolar gyre Revelle buffer factor